2017
DOI: 10.1186/s12879-017-2682-4
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition and clearance of multidrug resistant Acinetobacter baumannii on healthy young adults concurrently burned in a dust explosion in Taiwan: the implication for antimicrobial stewardship

Abstract: BackgroundInformation is limited about the effect of restricted carbapenem use on clearance of multi-drug resistant Acinetobacter baumannii (MDRAB). We sought to determine the time effect of antibiotic exposure on multi-drug resistant Acinetobacter baumannii (MDRAB) acquisition and clearance.MethodsWe conducted a retrospective observational study at the intensive care units of a tertiary medical center. Forty-two of a cohort of previously healthy young adults who were concurrently burned by a dust explosion wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 31 publications
(33 reference statements)
1
14
0
6
Order By: Relevance
“…More information might be provided if molecular epidemiological surveillance was available. However, the overall data from our study showed that the incidence of A. baumannii isolates resistant to carbapenem was relatively low, and the result was similar to the incidence of CRABs (21%) reported by two similar groups, but treated in different hospitals [23,24]. Apart from CRAB, the resistance rates for other GNB were also quite low, such as carbapenem-resistant Enterobacteriaceae (0.3-2.4%) and pandrug-resistant P. aeruginosa (0.3%).…”
Section: Microbes and Drug-resistant Bacteriasupporting
confidence: 86%
See 1 more Smart Citation
“…More information might be provided if molecular epidemiological surveillance was available. However, the overall data from our study showed that the incidence of A. baumannii isolates resistant to carbapenem was relatively low, and the result was similar to the incidence of CRABs (21%) reported by two similar groups, but treated in different hospitals [23,24]. Apart from CRAB, the resistance rates for other GNB were also quite low, such as carbapenem-resistant Enterobacteriaceae (0.3-2.4%) and pandrug-resistant P. aeruginosa (0.3%).…”
Section: Microbes and Drug-resistant Bacteriasupporting
confidence: 86%
“…Recently one study showed that the overwhelming majority of bloodstream pathogens were GNB isolates typically isolated within 2 weeks after the burn. During 15-28 days after burn, A. baumannii was the most common causative pathogen, while Chryseobacterium spp., S. maltophilia, and R. mannitolilytica were most frequently isolated early (mean: 14.5 days) after the burn [24]. The proportion of the overall microbial isolates in this study showed a significant change in trend over time; in particular, hospitalization for more than 14 days (OR 4.5-9.8, p < 0.001).…”
Section: Main Risk Factors For Microbial Colonization and Infectionmentioning
confidence: 54%
“…Studies were published between 1994 and 2017 and combined data spanning from 1990 to 2015. The highest number of contributions came from France (two) and Turkey (two), while one study each was carried out in Australia, Brazil, Canada, Germany, Singapore, Spain and Taiwan . Studies ran for a median of 15 months (interquartile range 12–24) and analysed a total of 289 cases from a cohort of 2221 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Two (18%) studies included patients from an ICU only, two (18%) from a burn ICU and seven (64%) combined data on ICU patients with patients from the burn ward . Seven (64%) studies focused exclusively on A. baumannii , two (18%) on P. aeruginosa , one (9%) study on K. pneumoniae and one (9%) analysed Gram‐negative bacteria collectively . Five (45%) studies used molecular typing to identify bacterial clones .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation